Comparing Dynamics and Determinants of Severe Acute Respiratory Syndrome Coronavirus 2 Transmissions Among Healthcare Workers of Adult and Pediatric Settings in Central Paris. (14th July 2020) - Contejean, Adrien; Leporrier, Jérémie; Canouï, Etienne; Alby-Laurent, Fanny; Lafont, Emmanuel; Beaudeau, Lauren; Parize, Perrine; Lecieux, Fabienne; Greffet, Agnès; Chéron, Gérard; Gauzit, Rémy; Fourgeaud, Jacques; et al.
Abstract: Background: Healthcare workers (HCWs) have paid a heavy toll during the coronavirus disease 2019 (COVID-19) outbreak. Routes of transmission remain to be fully understood. Methods: This prospective study compared a 1500-bed adult and 600-bed pediatric setting of a tertiary-care university hospital located in central Paris. From 24 February until 10 April 2020, all symptomatic HCWs were screened for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on a nasopharyngeal swab. HCWs screened positive were questioned on their profession, symptoms, and occupational and nonoccupational exposures to SARS-CoV-2. Results: Among 1344 HCWs tested, 373 were positive (28%) and 336 (90%) corresponding questionnaires were completed. Three hospitalizations and no deaths were reported. Most HCWs (70%) had patient-facing occupational activities (22% in COVID-19 dedicated units). The total number of HCW cases peaked on 23 March, then decreased slowly, concomitantly with a continuous increase of compliance to preventive measures (including universal medical masking and personal protective equipment [PPE] for direct care to COVID-19 patients). Attack rates were of 3.2% and 2.3% in the adult and pediatric settings, respectively ( P = .0022). In the adult setting, HCWs more frequently reported exposure to COVID-19 patients without PPE (25% vs 15%, P = .046). Report of contacts with children attending out-of-home care facilities dramatically decreased over the study period. Conclusions: Universal masking, reinforcement of hand hygiene, and PPE with medical masks for patients' care allowed protection of HCWs and containment of the outbreak. Residual transmissions were related to persistent exposures with undiagnosed patients or colleagues and not to contacts with children attending out-of-home care facilities. Abstract : Compliance to control measures allowed containment of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak in healthcare workers (HCWs). Medical masks in most situations and N95/FFP2 in aerosol-generating procedures largely protect HCWs against SARS-CoV-2. Small-sized childcare facilities may be acceptable to help HCWs stay at work.